Discovery of Alpha-Gal-Containing Antigens in North American Tick Species Believed to Induce Red Meat Allergy - Crispell, Gary; Commins, Scott P.; Archer-Hartman, Stephanie A.; Choudhary, Shailesh; Dharmarajan, Guha; Azadi, Parastoo; Karim, Shahid (Frontiers in immunology, 2019)
Development of specific IgE antibodies to the oligosaccharide galactose-α-1, 3-galactose (α-gal) following tick bites has been shown to be the source of red meat allergy. In this study, we investigated the presence of α-gal in four tick species: the lone-star tick ( ), the Gulf-Coast tick ( ), the American dog tick ( ), and the black-legged tick ( ) by using a combination of immunoproteomic approach and, carbohydrate analysis. Anti-α-gal antibodies identified α-gal in the salivary glands of both and , while and appeared to lack the carbohydrate. PNGase F treatment confirmed the deglycosylation of N-linked α-gal-containing proteins in tick salivary glands. Immunolocalization of α-gal moieties to the salivary secretory vesicles of the salivary acini also confirmed the secretory nature of α-gal-containing antigens in ticks. ticks were fed on human blood (lacks α-gal) using a silicone membrane system to determine the source of the α-gal. N-linked glycan analysis revealed that and have α-gal in their saliva and salivary glands, but contains no detectable quantity. Consistent with the glycan analysis, salivary samples from and stimulated activation of basophils primed with plasma from α-gal allergic subjects. Together, these data support the idea that bites from certain tick species may specifically create a risk for the development of α-gal-specific IgE and hypersensitivity reactions in humans. Alpha-Gal syndrome challenges the current food allergy paradigm and broadens opportunities for future research.